Digital Self-Harm Among Adolescents - a literature review - Karolina Krochmal; Aleksandra Kujawa; Kacper Stępniak; Jan Wilk; Paulina Krzeszowska; Radosław Kuźma; Karolina Marrodán-Wojtczak; Jakub Jarmołowicz; Adrianna Samoraj; Jakub Zajączkowski (Journal of Education, Health and Sport)
Introduction: